KEPEMIMPINAN VISIONER KEPALA SEKOLAH DALAM MENINGKATKAN DISIPLIN KERJA GURU DI SMP NEGERI 5 PONTIANAK - Setiawati, Yulita; Wicaksono, Luhur; Wahyudi, Wahyudi (Universitas Tanjungpura, 2024)
The teacher's work discipline is the behavior and attitude of obedience and adherence to regulations. Visionary leadership is a leader who has a vision for the future. Research to analyze and describe the visionary leadership of school principals in improving teacher work discipline at SMP Negeri 5 Pontianak. The form of this research is a case study with a qualitative approach. Methods of data collection through interviews, observation, and documentation. The process of data analysis uses the Miles and Huberman model, namely data processing is carried out sequentially starting from data reduction, data exposure, conducting verification. Data validity checking techniques use extended observations, increased persistence, triangulation, and member checks. The results of this study are; 1) Principals improve teacher work discipline through exemplary, building communication, and social-human relations that are harmonious and have goals and abilities; 2) Visionary leadership has the ability to determine the school's vision and mission and dare to make decisions. 3) The visionary leadership of the school principal can improve the work discipline of teachers with exemplary leadership, human relations, goals have the ability to formulate vision and mission, dare to make decisions. The conclusion in this study is that the visionary leadership of the principal can improve the work discipline of teachers at SMP Negeri 5 Pontianak.